Peran Perempuan Menurut Muhammad Asad dalam Tafsir The Message Of The Qur’an - Fitriati, Khairunnisa (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
In the Jailiyah order, women are placed as the second human being, they are below the superiority of men. Overall, women are regarded as inferior and unfairly treated in many aspects of life. This problem repeats itself until it changes the public's understanding of the concept of sex that is actually the same as the gender concept that is the result of social construction. The interpretation of the Qur'an has an important role in shaping human understanding. The true interpretation must strive to understand the messages contained in it in a comprehensive and unfragmented manner. This research is a research library research and is included in the category of study tafsir maudhu’i. In this research it is produced that the concept of the role of women in the interpretation